2020
DOI: 10.21203/rs.3.rs-18150/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic diversity analysis of a Flax (Linum usitatissimum L.) global collection

Abstract: Abstract Background A sustainable breeding program requires a minimum level of germplasm diversity to provide varied options for the selection of new breeding lines. To maximize genetic gain of the North Dakota State University (NDSU) flax breeding program, we aimed to increase the genetic diversity of its parental stocks by incorporating diverse genotypes. For this purpose, we analyzed the genetic diversity, linkage disequilibrium, and population sub-structure of 350 … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 64 publications
(82 reference statements)
1
2
0
Order By: Relevance
“…The genetic structure observed in this experiment is consistent with what was establish in previous works, which demonstrated the clustering of accessions attributed to their eco-geographic origin [31,54]. The relatively high differentiation and high concentration of private haplotypes in populations dominated by South Asian accessions may suggest the adaptation of the crop to warm regions [55,56]. This is unlike the cool and/or temperate habitats where flax is widely grown [57].…”
Section: Genetic Structure and Differentiationsupporting
confidence: 90%
See 1 more Smart Citation
“…The genetic structure observed in this experiment is consistent with what was establish in previous works, which demonstrated the clustering of accessions attributed to their eco-geographic origin [31,54]. The relatively high differentiation and high concentration of private haplotypes in populations dominated by South Asian accessions may suggest the adaptation of the crop to warm regions [55,56]. This is unlike the cool and/or temperate habitats where flax is widely grown [57].…”
Section: Genetic Structure and Differentiationsupporting
confidence: 90%
“…This is unlike the cool and/or temperate habitats where flax is widely grown [57]. Flax in this warm South Asian region might also be adapted to short-day photoperiod given that flax accessions from this region differ from the common flax adapted to grow under the long-day seasons of most cooler regions [56,58]. In a similar way, the higher rate of private haplotypes in the Abyssinian population may be attributable to adaptation of the crop to the equatorial re-gion, with equinox effects, elevation-induced cool temperate climate and windstorms [31,59].…”
Section: Genetic Structure and Differentiationmentioning
confidence: 99%
“…ProSpecieRara ensures the preservation of rare traditional varieties 55 . Furthermore, studies have shown that linseed varieties have higher genetic variability than fiber flax and should therefore be considered as valuable genetic resources 56,57 .…”
Section: Methodsmentioning
confidence: 99%